Thermodynamic Uncertainty Relations in Driven Open Quantum Systems: Bounds on Precision and Dissipation Beyond the Markovian Approximation - Sofia Pereira; Carlos Lopes; Marta Carvalho (Journal of Tecnologia Quantica, 2026)
Thermodynamic Uncertainty Relations in Driven Open Quantum Systems: Bounds on Precision and Dissipation Beyond the Markovian Approximation